2021
DOI: 10.3389/fimmu.2021.618150
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Randomized Clinical Trial and Mechanistic Studies Using Improved Probiotics to Prevent Oral Mucositis Induced by Concurrent Radiotherapy and Chemotherapy in Nasopharyngeal Carcinoma

Abstract: Earlier evidence has proven that probiotic supplements can reduce concurrent chemoradiotherapy (CCRT)-induced oral mucositis (OM) in nasopharyngeal cancer (NPC). The incidence of severe OM (grade 3 or higher) was the primary endpoint in this study. We first enrolled 85 patients with locally advanced NPC who were undergoing CCRT. Of them, 77 patients were finally selected and randomized (1:1) to receive either a probiotic cocktail or placebo. To investigate the protective effects and the mechanism of probiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 70 publications
1
71
0
1
Order By: Relevance
“…Table 4 illustrates examples from human clinical trials [ 131 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. Not surprisingly, the best outcomes occur when there is a clear understanding of the specific microbes, genes, metabolic changes, and installation conditions that are needed to support microbiome-driven physiological benefits.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…Table 4 illustrates examples from human clinical trials [ 131 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. Not surprisingly, the best outcomes occur when there is a clear understanding of the specific microbes, genes, metabolic changes, and installation conditions that are needed to support microbiome-driven physiological benefits.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…In a phase II randomized clinical trial on the effectiveness of a probiotic cocktail on oral mucositis in advanced nasopharyngeal cancer patients undergoing concurrent chemoradiotherapy, similar results were found. For instance, the relative abundance of probiotics, such as Lactobacillus, Bifidobacterium and Akkermansia, decreased, while the abundance of harmful bacteria, such as Clostridium, Enterococcus, and Enterobacter increased [25]. A systematic review by Yixia and colleagues summarized that a chemotherapy regimen (including one or more of 5-fluorouracil/FU, capecitabine, oxaliplatin, irinotecan and folinic acid) and surgery may lead to distinct alterations in the gut microbiota composition in colorectal cancer patients particularly in Proteobacteria phylum [26].…”
Section: Intestinal Microbiota Dysbiosis In Cancer Patientsmentioning
confidence: 99%
“…As reviewed by Badgeley et al, supplementation with probiotics has several benefits for cancer patients such as enhancing cancer cell apoptosis, reducing chemotherapy toxicity and modulating host immune response [93]. A phase II randomized clinical trial recently conducted by Xia et al confirmed that a probiotic cocktail can reduce concurrent chemoradiotherapy-induced oral mucositis in nasopharyngeal cancer patients [25]. Interestingly, fecal microbiota transplantation could be used to treat severe Clostridioides difficile colitis in a pediatric patient with non-Hodgkin lymphoma [94].…”
Section: Prophylactic Effect Of Antibiotics Probiotics and Natural Productsmentioning
confidence: 99%
“…For this to be realised, appropriate infrastructure such as tissue and biome banking, and comprehensive data collection with skilled bioinformatics (likely with artificial intelligence and machine learning capacity) is needed to identify meaningful biomarkers with clinical utility. Although sequencing the microbiota genome (through technology such as 16S rRNA) is a relatively new approach to mucositis research, it has already yielded exciting findings that could be applied to personalised medicine and has the advantage of being a modifiable risk factor through microbial-related therapies such as ultra-narrow antibiotics, prebiotics, second-generation probiotics, and metabolites now being investigated in clinical trials [21][22][23]. Consequently, one of the major opportunities going forward is to begin to assess the impact of multiple mechanistic variables-genomics, proteomics, metabolomics, microbiomics-simultaneously in a systems biology approach to enact true personalised medicine in supportive care.…”
mentioning
confidence: 99%